Sex-Specific Differences in HLA Antibodies after Pneumococcal Vaccination in Kidney Transplant Recipients - Monika Lindemann; Simon Oesterreich; Benjamin Wilde; Ute Eisenberger; Nils Muelling; Peter A. Horn; Falko M. Heinemann; Oliver Witzke (Vaccines, 2019)
In transplant recipients vaccination against Streptococcus pneumoniae is recommended to reduce mortality from invasive pneumococcal disease. It is still debated if vaccination in transplant recipients triggers alloresponses. Therefore, it was our aim to define if vaccination with Prevenar 13®, a 13-valent, conjugated pneumococcal vaccine (Pfizer, New York, NY, USA) that acts T cell dependently, induces human leukocyte antigen (HLA) antibodies in clinically stable kidney transplant recipients. Forty-seven patients were vaccinated once with Prevenar 13® and HLA antibodies were determined prior to vaccination and at month 1 and 12 thereafter. In parallel, pneumococcal IgG antibodies were measured. Using Luminex™ Mixed Beads technology (One Lambda/Thermo Fisher, Canoga Park, CA, USA) we observed overall no change in HLA antibodies after vaccination. Pneumococcal antibodies increased significantly at month 1 (p < 0.0001) and remained elevated at month 12 (p < 0.005). A more detailed analysis of HLA antibodies showed that in 18 females HLA class I and II antibodies increased significantly at month 1 and 12 (p < 0.05); whereas in 29 males HLA class I and II antibodies tended to decrease. Using Luminex™ Single Antigen Beads assay, no de novo donor-specific HLA antibodies were detected after vaccination. In conclusion, the current data indicate that females may be more susceptible to the induction of (non-specific) HLA antibodies after vaccination.